REVIEW PENGARUH PENGGUNAAN SURFAKTAN PADA KARAKTERISTIK SEDIAAN ORODISPERSIBLE FILM (ODF) OBAT BERKELARUTAN RENDAH DALAM AIR: SIFAT DISINTEGRASI DAN DISOLUSI - Nining, Nining (Jurnal Penelitian Farmasi & Herbal, 2023)
Orodispersible film (ODF) is a drug delivery gaining widespread acceptance because it disintegrates quickly and can be self-administered. ODF has the advantage of increasing the active pharmaceutical ingredient (API) effectiveness by rapid dissolution in the oral cavity after direct contact with saliva. One of the components of ODF that influences the physical characteristics and dissolution of low-soluble drugs in water is surfactant. This material acts as a wetting or dispersing agent so the film can quickly disintegrate and release API. The method used is searching for international journal data using the Google Scholar. The surfactants reported to have been used in the ODF formulation are L-arginine, poloxamer 407, tween 80, and sodium dodecyl sulfate. In general, surfactant usage significantly affects the disintegration behavior of the film and API release. This behavior is caused by reducing the interfacial tension between phases by surfactants, which causes increased solid surface wetting and helps speed up the film disintegration and API dissolution from the ODF matrix. The conclusion is that surfactant usage with the appropriate type and concentration will help improve the ODF quality, especially in the disintegration properties of the dosage form and API dissolution.